Emily and Einstein - Lee, Linda Francis (New York : St. Martin's Press, 2011)
Sandy Portman and Emily Barlow seem to lead a perfect life. Sandy is a successful businessman from an old-money family, and Emily, beautiful and smart, is quickly gaining respect in her career as a book editor. But Sandy is keeping a few secrets from Emily, and is hit by a car and killed before he has a chance to reveal the truth. In a Dickensian turn of events, he's given an otherworldly chance to make amends as a dog named Einstein.
Keywords: Husbands -- Fiction -- Death; Dogs -- Fiction; Bereavement -- Fiction; Grief -- Fiction; Upper West Side (New York, N.Y.) -- Fiction; Love stories